2012
DOI: 10.1590/s2179-64912012000400004
|View full text |Cite
|
Sign up to set email alerts
|

A influência dos aspectos cognitivos e dos processos auditivos na aclimatização das próteses auditivas em idosos

Abstract: All subjects were acclimatized, because there was improvement in speech recognition following the use of hearing aids. Subjects with cognitive problems present poorer performance in speech recognition processes with dichotic listening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 24 publications
1
9
1
15
Order By: Relevance
“…The same occurred in a study that used the Digit Symbol Substitution Test (DSST) to evaluate cognitive factors, in which it was found an association between hearing loss and cognitive decline, highlighting that this fact was evident in losses with greater levels (24) . However, this study is in agreement with a study that was carried out with 60 elderly patients in which no correlation was found between hearing loss and cognition (23) . However, this study evaluated individuals with moderate and moderately severe hearing loss.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The same occurred in a study that used the Digit Symbol Substitution Test (DSST) to evaluate cognitive factors, in which it was found an association between hearing loss and cognitive decline, highlighting that this fact was evident in losses with greater levels (24) . However, this study is in agreement with a study that was carried out with 60 elderly patients in which no correlation was found between hearing loss and cognition (23) . However, this study evaluated individuals with moderate and moderately severe hearing loss.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, a study of 60 elderly people, with the use of MMSE and the Alzheimer's Disease Assessment Scale (ADAS-Cog), found that the majority of the sample (61.7%) presented cognitive changes mainly in MMSE (23) . Regarding the relationship between cognition with hearing loss, the current study showed different results of a study (19) that evaluated cognitive performance in elderly people with MMSE and it found a correlation between the presence of hearing loss and abnormal results of MMSE, since the individuals with mild sensorineural hearing loss presented better cognitive performance than those ones with moderate and severe levels.…”
Section: Discussionmentioning
confidence: 99%
“…The study found performance changes in 20% of cases, a lower result than the 61% found in another study of 60 patients with already diagnosed hearing loss, candidates for selection and adaptation of hearing aids in a reference center for Audiology Health Care 16 .…”
Section: Discussioncontrasting
confidence: 62%
“…Moreover, the inability to perform binaural synthesis of what was heard may be responsible for the complaint of difficulties in understanding the auditory information, especially in noisy places 16 .…”
Section: Discussionmentioning
confidence: 99%
“…However, another study has shown an association of the results on Dichotic Digit test with cognitive tests. They show that the better the cognitive performance, the better the results on auditory processing tests of the subjects (22) . Several studies mention the relationship between cognition and presbycusis (23,24,25) , including, authors ponder that if hearing loss actually has such a remarkable influence on cognitive decline and recommend that the hearing aids for the elderly should be strongly encouraged and fitted as soon as possible (26) .…”
Section: The Results Obtained On Different Tests (Rgdt Dps -Right Eamentioning
confidence: 95%